Tuning product selectivity in the catalytic oxidation of glycerol by employing metal-ZSM-11 materials - Diguilio, Eliana (2020)
Copper and chromium supported on ZSM-11 (MEL-type structure) microporous zeolites were investigated as catalysts for glycerol oxidation towards dihydroxyacetone and lactic acid. ZSM-11 was synthesized by hydrothermal crystallization. Subsequently, alkaline treatment of desilication was carried out in order to generate zeolites with micro-mesoporosity. Ion exchange with ammonium chloride was performed to recover acidic sites and then, Cr(III) and Cu(II) species were incorporated onto these materials. Finally, thermal treatment at 500 °C was carried out. These materials were characterized by different techniques and then evaluated in the glycerol oxidation reaction by employing H2O2 as an oxidizing agent. The maximum conversion of glycerol (∼70%) was reached over the Cr?ZSM-11 catalyst with a selectivity of ∼28% towards dihydroxyacetone. Meanwhile, Cu-ZSM-11 offered 50% glycerol conversion with a selectivity of 68% towards lactic acid. In both the cases, the optimal reaction conditions were studied to maximize the selectivity towards the products mentioned above.